Emplacement ages, geochemical and Sr–Nd–Hf isotopic characterization of Mesozoic to early Cenozoic granitoids of the Sikhote-Alin Orogenic Belt, Russian Far East: Crustal growth and regional tectonic evolution. (1st November 2015) - Jahn, Bor-ming; Valui, Galina; Kruk, Nikolai; Gonevchuk, V.; Usuki, Masako; Wu, Jeremy T.J.
Graphical abstract: Highlights: Age and geochemical study was conducted on granitoids from the Sikhote-Alin accretionary orogenic belt. Zircon dating revealed that the granitoids were emplaced during a period from 130 to 56 Ma (Cretaceous to Paleogene). The granitic magmas were generated by partial melting of mixed lithologies-subducted accretionary complexes and hidden basement rocks. Sr–Nd–Hf isotopic data indicate an important role of the mantle component (36–77%) in the generation of the granitic rocks. The geologic correlation between Sikhote-Alin and SW Japan is supported by the present study. Abstract: The Sikhote-Alin Range of the Russian Far East is an important accretionary orogen of the Western Pacific Orogenic Belt. In order to study the formation and tectonic evolution of the orogen, we performed zircon U–Pb dating, as well as geochemical and Sr–Nd–Hf isotopic analyses on 24 granitoid samples from various massifs in the Primorye and Khabarovsk regions. The zircon dating revealed that the granitoids were emplaced from 131 to 56 Ma (Cretaceous to Paleogene). In the Primorye Region, granitoids in the coastal Sikhote-Alin intruded the Cretaceous Taukha Accretionary Terrane from ca. 90 to 56 Ma, whereas those along the Central Sikhote-Alin Fault zone intruded the Jurassic Samarka Accretionary Terrane during ca. 110–75 Ma. The "oldest" monzogranite (131 Ma) was emplaced in the Lermontovka area of the NW Primorye Region. Granitoid massifs along the Central Sikhote-Alin Fault zone in the Khabarovsk Region formed from 109 to 58 Ma. Thus, the most important tectonothermal events in the Sikhote-Alin orogen took place in the Cretaceous. Geochemical analysis indicates that most samples are I-type granitoids. They have initial 87 Sr/ 86 Sr ratios ranging from 0.7040 to 0.7083, and initial Nd isotopic ratios, expressed as ε Nd ( t ) values, from +3.0 to −5.0 (mostly 0 to −5). The data suggest that the granitoid magmas were generated by partial melting of sources with mixed lithologies, including the subducted accretionary complex ± hidden Paleozoic-Proterozoic basement rocks. Based on whole-rock Nd isotopic data, we estimated variable proportions (36–77%) of juvenile component (=mantle-derived basaltic rocks) in the generation of the granitic magmas. Furthermore, zircon Hf isotopic data ( ε Hf ( t ) = 0 to +15) indicate that the zircon grains crystallized from melts of mixed sources and that crustal assimilation occurred during magmatic differentiation. The quasi-continuous magmatism in the Sikhote-Alin orogen suggests that the Paleo-Pacific plate subduction was very active in the Late Cretaceous. The apparently regular progression of granitic intrusion ages from 80 to 56 Ma in the Taukha Terrane may reflect oblique underflow of the Paleo-Pacific plate beneath the Eurasian continental margin. Subduction was not only manifested by granitic intrusion, but also by abundant silicic volcanism. The Late Cretaceous Paleo-Pacific plate motion probably changed from parallel or sub-parallel to oblique relative to the continental margin of the Sikhote-Alin, leading to the change of magmatic source region and geochemical characteristics of the derived igneous rocks. Late Cretaceous rapid sea-floor spreading at ca. 100 Ma induced highly active subduction and led to voluminous magmatism in the entire Circum-Pacific realm. Finally, the present age and isotopic study lends support to the hypothesis of geologic and tectonic correlation between Sikhote-Alin and SW Japan.